2018
DOI: 10.14202/vetworld.2018.25-29
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory properties of a wound dressing combination of zinc oxide and turmeric extract

Abstract: Aim:The aim of this study was to determine the effect of a wound dressing consisting of a zinc oxide with turmeric extract combination as an anti-inflammatory on the healing process through the expression of MAC387 and cyclooxygenase-2 (COX-2).Materials and Methods:Forty Wistar rats were divided into four control and four treatment groups (n=5). On day 1, a 6 mm×6 mm square of skin in the area of the vertebralis thoracis was excised from all subjects. The wound was then dressed with a combination of zinc oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The ZO as an anti‐inflammatory agent by decreasing the malondialdehyde level and blocking the pro‐inflammatory cytokines including interleukin‐1 (IL‐1), interleukin‐1Beta (IL‐1β), and tumor necrosis factor‐alpha (TNF‐α) decreases the inflammatory response in burned wound. [ 100,101 ] In addition, other reports further revealed that ZO mediated the toll‐like receptors/NF‐κB inflammatory signaling pathway, which is associated with decreased inflammation. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…The ZO as an anti‐inflammatory agent by decreasing the malondialdehyde level and blocking the pro‐inflammatory cytokines including interleukin‐1 (IL‐1), interleukin‐1Beta (IL‐1β), and tumor necrosis factor‐alpha (TNF‐α) decreases the inflammatory response in burned wound. [ 100,101 ] In addition, other reports further revealed that ZO mediated the toll‐like receptors/NF‐κB inflammatory signaling pathway, which is associated with decreased inflammation. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the condition of control group on day 7 to still be in the inflammatory phase due to NF-κB releasing TNFα as a pro-inflammatory cytokine [2]. The A3 and B3 groups which were treated with a zinc oxide and eugenol dressing showed a lower expression of TNFα than the control group.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequent immunohistochemistry evaluation adhered to the previously described method [2]. The procedural steps were completed with minor modifications [11].…”
Section: Immunohistochemistry Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have proven that the combination of zinc oxide wound dressing and the C. longa extract can hasten the wound healing process by decreasing the expression of toll-like receptors-2, nuclear factor κB (NF-κB), and tumor necrosis factor α in the inflammatory phase. [ 8 ] The nature of zinc oxide as antibacterial, disinfectant, and drying agent is the reason of zinc oxide use in medicine field. The previous experiments showed that the nature of zinc oxide can hasten the wound healing.…”
Section: Introductionmentioning
confidence: 99%